2011
DOI: 10.1007/s10144-010-0258-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and cause‐specific mortality of female Rocky Mountain elk exposed to human activity

Abstract: Animal populations are becoming increasingly exposed to human activity as human populations expand and demand for energy resources (e.g., coal, oil and natural gas) increases. We initiated this study to document survival and cause-specific mortality patterns of female Rocky Mountain elk (Cervus elaphus) exposed to increasing levels of human activity. We fitted 184 females with VHF or GPS collars over 4 years and used the Kaplan-Meier survival estimator to calculate annual survival rates. We used multinomial lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 31 publications
6
44
0
Order By: Relevance
“…Previous studies have found that higher hunting pressure and hunter accessibility negatively affect wapiti survival at the scale of seasonal home ranges, but that there are no significant associations between cover and survival at this scale (McCorquodale, Wiseman, & Marcum, 2003;Unsworth, Kuck, Scott, & Garton, 1993). Nor are there significant associations between wapiti survival and the amount of cover at the scale of weekly home ranges (Webb et al, 2011). In contrast, a finer-scale analysis has revealed that bold wapiti individuals, with higher rates of movement, weaker response to human activity and greater use of open terrain, are more likely to be harvested than shy individuals (Ciuti et al, 2012).…”
mentioning
confidence: 71%
“…Previous studies have found that higher hunting pressure and hunter accessibility negatively affect wapiti survival at the scale of seasonal home ranges, but that there are no significant associations between cover and survival at this scale (McCorquodale, Wiseman, & Marcum, 2003;Unsworth, Kuck, Scott, & Garton, 1993). Nor are there significant associations between wapiti survival and the amount of cover at the scale of weekly home ranges (Webb et al, 2011). In contrast, a finer-scale analysis has revealed that bold wapiti individuals, with higher rates of movement, weaker response to human activity and greater use of open terrain, are more likely to be harvested than shy individuals (Ciuti et al, 2012).…”
mentioning
confidence: 71%
“…It appears that male deer respond spatially to temporal risk from hunters in general (mean response and trends), but also appear to respond in situation-specific manners (large variation around the mean). In elk, modified behavior and resource selection have been found to reduce the probability of mortality (Webb et al 2011c;Dzialak et al 2011). It appears that adult male deer are able to adopt strategies that lend themselves to avoiding detection by hunters (Little et al 2016), so these strategies likely could increase fitness through increased survival when deer are not at risk of harvest.…”
Section: Figmentioning
confidence: 99%
“…We used Spatial Analyst in ArcGIS ® 10.0 to calculate raster values and to extract values from raster data to location data for all covariates. See Visual Learning Systems, Inc. (2008) and Webb et al (2011) for details on using Feature Analyst, and Dzialak et al (2011a) for a more complete description of covariates, data sources, and methods.…”
Section: Spatial Variables: Landscapementioning
confidence: 99%